Fitorremediação de rejeito salino proveniente da osmose reversa em sistema hidropônico de cultivo de mudas de Eucalyptus dunnii - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
The reverse osmosis system is an alternative used to supply the high demand for drinking water in places with hydric stress. This process produces a residue called brine which has high concentrations of total dissolved solids. In order to remove the salts, we treated the brine by phytoremediation with eucalyptus seedlings (Eucalyptus dunnii) which were kept in a hydroponic system on a bench scale, inside a greenhouse. pH, dissolved oxygen, total dissolved solids, salinity, temperature and electrical conductivity were the parameters monitored daily, for the treatments using brine with different concentrations of electrical conductivity (7.6, 12 and 16.1 mS cm-1). Results about seedling growth performance (plant shoot height, number of leaves, stem diameter and leaf area), physiological attributes (chlorophyll, stomatal conductance, photosynthesis, leaf transpiration and concentration carbon in the mesophile) and physical-chemical analyzes of the liquid (input and output), after 50 days of the experiment, were collected and analyzed. The treatment which received brine with the lowest electrical conductivity concentration (7.6 mS cm-1) presented salts removal greater than 60% during the first month, as well as in the control treatment. The brine treatment with electrical conductivity concentrations above 7.6 mS cm-1 presented dead plants from the 25th day and low morphological development compared to the control and the lowest concentration treatments. The survival of the eucalyptus seedlings in the brine treatment with electrical conductivity concentration of 16.1 mS cm-1 shows tolerance of the species to the salt.
Keywords: Água Salobra; Espécie Florestal; Sustentabilidade; Brackish Water; Forest Species; Sustainability; CNPQ::ENGENHARIAS::ENGENHARIA SANITARIA